Exploring Community Trust and Attitudes Towards COVID-19 Vaccination in Banda Aceh, Indonesia - Husna, Cut; Charyasti, Desvi; Darliana, Devi (TDMRC, Universitas Syiah Kuala, 2023)
To mitigate COVID-19 infections and safeguard the community against infection risks, the Indonesian government initiated a national COVID-19 vaccination program. It was observed that the community exhibited a mix of acceptance and reluctance toward the vaccination program due to varying information disseminated through multiple media sources, particularly concerning the issue of halal vaccines and their potential adverse effects. The decision to undergo COVID-19 vaccination is closely tied to the community's confidence in the vaccine's efficacy. Vaccine hesitancy poses a significant obstacle in the battle against the COVID-19 pandemic. Several factors contributing to the community's trust in the vaccine encompass shared norms and values, willingness to endorse, and perceived efficacy. The objective of this study was to identify the relationship between the community's trust in the effectiveness of the COVID-19 vaccine and their attitudes toward receiving vaccinations in the region of Banda Aceh. To achieve this, a correlational study with a cross-sectional design was conducted. The study's sample consisted of the community residing in the Kuta Alam sub-district of Banda Aceh, totalling 266 participants. Data collection was facilitated through the administration of the